Quasicoherent modes on the COMPASS tokamak. (10th April 2015) - Melnikov, A V; Markovic, T; Eliseev, L G; Adámek, J; Aftanas, M; Bilkova, P; Boehm, P; Gryaznevich, M; Imrisek, M; Lysenko, S E; Medvedev, S Y; Panek, R; et al.
Abstract: Multiple quasicoherent electromagnetic modes with steady-state frequency and different nature and location were observed in the COMPASS tokamak ( R = 0.56 m, < a >  = 0.2 m) at B t = 1.14 T with Co-NBI ( P NBI = 0.2–0.5 MW, E b = 32 keV) at frequencies 5 kHz <  f  < 250 kHz. Modes were observed in both low and high confinement (L- and H-modes) plasmas. Lower frequency modes with f  < 50 kHz were identified as low m tearing and kink MHD modes, while higher frequency modes with 50 kHz <  f  < 250 kHz were considered as having Alfvénic nature. Unexpectedly, such modes were only observed in the H-mode, both in neutral beam injector-assisted and Ohmic, so the mode driving force is not yet clear. Using the linear MHD code KINX, we initially identified the observed mode with a ballooning structure is as beta induced Alfvén eigenmode (BAE) with m, n  < 5, while an antiballooning mode is initially identified as toroidal Alfvén eigenmode (TAE) with m, n  < 9.